SELECTION OF SUITABLE DILUENTS FOR BACTERIOLOGICAL EXAMINATION OF FISHERY PRODUCTS - THAMPURAN, NIRMALA; IYER, H KRISHNA; IYER, K MAHADEVA (Fishery Technology, 2017)
For raw, iced and frozen samples of fish and prawn, significant difference was observed in total plate counts done with various diluents, the significance level ranging from 5% to 0.1 % . For raw fish, N-saline, seawater and quarter strength Ringers’ solution gave maximum total plate counts. In the case of iced-fish, n-saline yielded highest total plate counts. For frozen samples, however, peptone water and n-saline gave good recoveries. Trials with suitable ecombinations of diluents showed that though some of them were as good as the control, name!y n-saline, none were superior in any way.